A Retrospective Cohort Study on Chronic Opioid Use After Geriatric Hip Fracture Surgery—Risk Factors, Trends, and Outcomes. Issue 6 (15th March 2023) - Stone, Julia M.; Pujari, Amit; Garlich, John; Lin, Carol
Abstract : Introduction: The purpose of this study is to identify the risk factors for prolonged opioid use after surgery in geriatric hip fracture patients and the effects of prolonged use on mortality and readmission rates. Methods: An institutional registry was queried for all patients older than 65 years who underwent surgical treatment of a hip fracture between January 2016 and June 2017. Using the Controlled Substance Utilization Review and Evaluation System (CURES), we identified patients who had filled an opioid prescription within 3 months of hospital admission as opioid exposed and patients without a history of opioid use as opioid naïve (ON). Results: Of 500 patients who underwent hip-fracture surgery during the study period, a total of 322 had complete Controlled Substance Utilization Review and Evaluation System data. 36.0% (116) were OE, and 64.0% (206) were ON. 23.0% (74) patients filled an opioid prescription 6 months after surgery, 59.5% (44) were OE, and 40.5% (30) were ON. OE and patients on antidepressants were more likely to continue opioids at 6 months. Age, sex, fracture pattern, implant, benzodiazepine use, smoking, and alcohol status were not notable risk factors for prolonged opioid use. Antidepressant use was a risk factor for readmission within 90 days. Previous opioid exposure predicted mortality within 6 months. Discussion: Opioid use in geriatric hip fracture patients is high both preoperatively and postoperatively. Opioid exposed patients and patients on antidepressants are more likely to continue opioids at 6 months. A substantial proportion of ON patients became prolonged opioid users. Although prolonged opioid use postoperatively did not increase the risk of readmission or death, antidepressant use predicted readmission and previous opioid exposure predicted mortality. By identifying predictors of prolonged postoperative opioid use in geriatric hip fracture patients, we can better prepare physicians and their patients on what to expect in the postoperative period. Level of evidence: Level III